An Iridium Complex with a Phosphine‐Pendant Silyl Ligand as an Efficient Catalyst for the (E)‐Selective Semihydrogenation of Alkynes. Issue 10 (14th March 2022) - Shen, Jingfeng; Usui, Ryosuke; Sunada, Yusuke
Abstract: Two iridium disilyl complexes that contain phosphine‐pendant silyl groups have been obtained from the reaction of [(cod)IrCl]2 with a disilane with phosphine pendants, (Ph2 PCH2 )R2 Si−SiR2 (CH2 PPh) (R=Me or Ph). The iridium complex with methyl‐substituted silyl moieties showed good catalytic performance in the ( E )‐selective semihydrogenation of various alkynes at room temperature under 1 atm of H2 without over‐reduction to the corresponding alkanes. Abstract : A coordinatively unsaturated iridium complex that contains two chelating silyl‐phosphine ligands, Ir(SiMe2 CH2 PPh2 )2 Cl, has been obtained from the reaction of [(cod)IrCl]2 with the corresponding disilane with phosphine pendants, (Ph2 PCH2 )Me2 Si−SiMe2 (CH2 PPh). This complex shows good catalytic performance in the ( E )‐selective semihydrogenation of various alkynes without over‐reduction to the corresponding alkanes.